Maternal treatment with a selective delta-opioid receptor agonist during gestation has a sex-specific pro-cognitive action in offspring: mechanisms involved - Dremencov, Eliyahu; Oravcova, Henrieta; Grinchii, Daniil; Romanova, Zuzana; Dekhtiarenko, Roman; Lacinova, Lubica; Jezova, Daniela (Frontiers in Pharmacology, 2024)
Background: There is growing evidence that the treatment of several mental disorders can potentially benefit from activation of delta-opioid receptors. In the future, delta-agonists with a safe pharmacological profile can be used for the treatment of mood disorders in pregnant women. However, the data on prenatal exposure to deltaopioid agonists are missing. The present study is aimed to test the hypothesis that the activation of delta-opioid receptors during gravidity has positive effects on the behaviour accompanied by changes in glutamate and monoamine neurotransmission.Methods: Gestating Wistar rats were chronically treated with a selective delta-agonist SNC80 or vehicle. Adult male and female offspring underwent novel object recognition (for the assessment of cognition) and open field (for the assessment of anxiety and habituation) tests, followed by in vivo electrophysiological examination of the activity of hippocampal glutamate and midbrain serotonin (5-HT) and dopamine neurons.We found that the maternal treatment with SNC80 did not affect the offspring's anxiety, habituation, and 5-HT neuronal firing activity. Female offspring of SNC80-treated dams exhibited improved novelty recognition associated with decreased firing rate and burst activity of glutamate and dopamine neurons.Maternal treatment with delta-opioid agonists during gestation may have a pro-cognitive effect on offspring without any negative effects on anxiety and habituation. The putative pro-cognitive effect might be mediated via mechanism(s) involving the firing activity of hippocampal glutamate and mesolimbic dopamine neurons.